Warifteine, an Alkaloid Purified from Cissampelos sympodialis, Inhibits Neutrophil Migration In Vitro and In Vivo - Thaline F. A. Lima; Juliana D. B. Rocha; Anderson B. Guimarães-Costa; José M. Barbosa-Filho; Débora Decoté-Ricardo; Elvira M. Saraiva; Luciana B. Arruda; Marcia R. Piuvezam; Ligia M. T. Peçanha (Journal of Immunology Research)
Cissampelos sympodialis Eichl is a plant from the Northeast and Southeast of Brazil. Its root infusion is popularly used for treatment of inflammatory and allergic diseases. We investigated whether warifteine, its main alkaloid, would have anti-inflammatory effect due to a blockage of neutrophil function. In vivo warifteine treatment inhibited casein-induced neutrophil migration to the peritoneal cavity but did not inhibit neutrophil mobilization from the bone marrow. Analysis of the direct effect of warifteine upon neutrophil adherence and migration in vitro demonstrated that the alkaloid decreased cell adhesion to P and E-selectin-transfected cells. In addition, fLMP-induced neutrophil migration in a transwell system was blocked by warifteine; this effect was mimicked by cAMP mimetic/inducing substances, and warifteine increased intracellular cAMP levels in neutrophils. The production of DNA extracellular traps (NETs) was also blocked by warifteine but there was no alteration on PMA-induced oxidative burst or LPS-stimulated TNFα secretion. Taken together, our data indicate that the alkaloid warifteine is a potent anti-inflammatory substance and that it has an effect on neutrophil migration through a decrease in both cell adhesion and migration.